Fake News Analysis of Supreme Court Decision from Linguistic Forensic and Critical Discourse Analysis Perspective - Thamrin, Husni; Dadang Sudana; Andika Dutha Bachari; R. Dian Dia-an Muniroh (UNIB Press, 2023)
This research purposes to know the results of the Supreme Court's decision on fake news by implementing linguistic forensic and critical discourse analysis based on Fairclough's 1995 grand theory approach. Some categories of analysis include representation, relations, identity, and sociocultural practices. Individual who break the law by spreading fake news may imprisonment. This is in accordance with the rules stated in Article 45A paragraph (2) of law number 19 of 2016, which amends law number 11 of 2008.The research method used is descriptive qualitative by collecting and analyzing data from defendants who are proven to have committed acts of insult and hatred of Ethnic Religion and Intergroup. The results of data analysis are in the form of representation of news information, power relations contained in it, the identity of the defendant formed, and the sociocultural practices that arise. Sociocultural practices that occur in this context, such as discrimination, controversy, and manipulation of information. The results of this study can become a foundation to sensitize the public about the dangers of fake news, encourage changes in creating truth in media practices, and increase defendants' awareness of the importance of justice in the criminal justice system.